Treatment of unlawful wealth which acquired by unlawful means from Islamic legal perspective - Hj Ibrahim, Badruddin; Laeba, Muhammad (2018)
This study examines the issue of treatment of unlawful wealth which acquired by unlawful means from Islamic Legal Perspective. The question is how Islam treats this type of wealth, whether a person who acquired the wealth by unlawful means has to return the wealth to its original owner or to give it to charity, the poor and needy or to destroy it. In case if a person has repented whether he/she is allowed to take possession of some portion from such wealth. The discussion focuses on the meaning of wealth which is acquired by unlawful means and its types; the treatment of Islamic legal system with respect to wealth which is acquired by unlawful means; and the issue of ownership of unlawful wealth after repentance. This study is a doctrinal analysis where the issues will be examined from the perspectives of the Qur’an and the Sunnah as primary sources of Islamic law and followed with the examination of the view of Muslim jurists of four well known schools of law as well as the view of contemporary Muslim scholars. In addition, the reference also will be made to legal opinions (fatawa) from some selected Muslim countries and some renowned Muslim scholars. It is expected that the study would provide a clear guideline regarding the handling of unlawful wealth that acquired by unlawful means under Islamic legal system.